Populational Differentiation in Boana bischoffi (Anura, Hylidae): Revisiting the Issue Using Molecular, Morphological, and Acoustic Data - Teixeira, Ana C. M.; Marcelino, Vanessa R.; Alexandrino, Joao; Haddad, Celio F. B. [UNESP]; Giaretta, Ariovaldo A. (Society for the Study of Amphibians and Reptiles, 2022)
Boana bischoffi was originally described from the Brazilian state of Rio Grande do Sul and has Boana multilineata from Sao Paulo as a junior synonym. The history of its nomenclature reflects the varying interpretation of the dorsal color pattern of the two different populations. We reevaluate the problem of taxonomic recognition of Boana multilineata based on molecular, morphometric, and acoustic data. The molecular data revealed two major clades that are partially concordant with the morphological and acoustic differentiation. Morphometric analyses revealed elements of differentiation between populations in snout-vent length (SVL) and head shape, which were patterns not detected previously. Discrimination considering call features was substantial, even complete in a discriminant analysis. Despite these differences, we refrain from resurrecting the name B. multilineata due to the existence of putative introgression zones, the effect of SVL in call dominant frequency, and lack of taxonomically relevant differences. Boana bischoffi might represent a case of incipient speciation.